Localization of the Center of the Intramuscular Nerve Dense Region of the Suboccipital Muscles: An Anatomical Study - Wang, Jie; Li, Yanrong; Wang, Meng; Yang, Shengbo (Frontiers in Neurology, 2022)
Purpose This study aimed to determine the body surface puncture position and depth of the center of the intramuscular nerve dense region in the suboccipital muscle to provide morphological guidance for accurate botulinum toxin A injection to treat headaches caused by increased suboccipital muscle tension. Methods Twenty-four cadavers aged 66.5 ± 5.3 years were studied. The curve line connecting occipital eminence or mastoid process and spinous process of the 7th cervical vertebrae was considered the longitudinal reference line (L) and horizontal reference line (H), respectively. Sihler's staining, barium sulfate labeling, and CT were employed. The body surface projection point of the center of the intramuscular nerve dense region was designated as P. The projection of the center of the intramuscular nerve dense region was in the opposite direction across the transverse plane and was recorded as P'. The intersections of the vertical line through point P and lines L and H were designated as PL and PH. The percentage position of the PH and PL points on the H and L lines and the depths of the center of intramuscular nerve dense regions were identified. Results Sihler's staining showed one intramuscular nerve-dense region in each suboccipital muscle. The PH of the center of the intramuscular nerve dense region was located at 51.40, 45.55, 20.55, and 43.50%. The PL was located at 31.38, 30.08, 16.91, and 52.94%. The depth of the center of the intramuscular nerve dense region was at 22.26, 22.54, 13.14, and 27.30%. These percentage values are all the means. Conclusion Accurately defining the body surface position and depth of the center of intramuscular nerve dense region in suboccipital muscles will help to improve botulinum toxin A to target localization efficiency for treating tension-type headache.